A Spatially Variable Time Series of Sea Level Change Due to Artificial Water Impoundment. Issue 7 (25th July 2020) - Hawley, William B.; Hay, Carling C.; Mitrovica, Jerry X.; Kopp, Robert E.
Abstract: The artificial impoundment of water behind dams causes global mean sea level (GMSL) to fall as reservoirs fill but also generates a local rise in sea level due to the increased mass in the reservoir and the crustal deformation this mass induces. To estimate spatiotemporal fluctuations in sea level due to water impoundment, we use a historical data set that includes 6, 329 reservoirs completed between 1900 and 2011, as well as projections of 3, 565 reservoirs that are expected to be completed by 2040. The GMSL change associated with the historical data (−0.2 mm yr −1 from 1900–2011) is consistent with previous studies, but the temporal and spatial resolution allows for local studies that were not previously possible, revealing that some locations experience a sea level rise of as much as 40 mm over less than a decade. Future construction of reservoirs through ~2040 is projected to cause a GMSL fall whose rate is comparable to that of the last century (−0.3 mm yr −1 ) but with a geographic distribution that will be distinct from the last century, including a rise in sea level in more coastal areas. The analysis of expected construction shows that significant impoundment near coastal communities in the coming decades could enhance the flooding risk already heightened by global sea level rise. Plain Language Summary: Filling a reservoir prevents that water from flowing back to the ocean, thus causing sea level to fall. But sea level does not change by the same amount everywhere: The mass of the water in the reservoir causes sea level to rise in locations near the reservoir but fall in locations that are farther away. We use databases that include the locations and capacities of reservoirs to estimate how constructing reservoirs has changed sea level and explore how these changes have varied in space and in time. We find that while constructing reservoirs since 1900 has caused sea level to fall on average, there are some locations that experience sea level rise by as much as 40 mm over a short period of time, usually only a few years. As more reservoirs are built, we expect this trend to continue. In fact, reservoirs that are currently being planned, if completed, will generate a sea level rise of a few millimeters in some low‐lying coastal areas. This rise would be in addition to the rise in sea level from many other known factors. Key Points: We present a spatially resolved time series of sea level due to reservoir construction from 1900–2040 Some locations in the past century have experienced a reservoir‐induced rise in sea level that exceeds 40 mm over less than a decade Future dam construction will cause patterns in sea level change that are different from the past and larger than current projections